Performance of waterjet on cutting maize stalks: A preliminary investigation - Hu, Hongnan; Li, Hongwen; Wang, Qingjie; He, Jin; Lu, Caiyun; Wang, Yingbo; Wang, Chunlei (International Journal of Agricultural and Biological Engineering, 2019)
Large amounts of crop stalks left in the field as a result of conservation agriculture cause blockage during no-till planting. To solve this issue, pure waterjet was used to cut off the maize stalks so that the rear furrow opener could pass through without blockage. In this investigation, an experimental study on depth of cut, which was the main performance indicator of pure waterjet on cutting maize stalks, was presented. A full factorial design with 200 tests was implemented with respect to three operation parameters, that is traverse speed, waterjet pressure, and standoff distance were considered as variables. An analysis of variance (ANOVA) was carried out in order to determine the statistical significance of individual operation parameters. Using multilinear stepwise regression analysis, a model to predict the cut of depth from the predicted pure waterjet operation to cut maize stalks was then developed. All three operation parameters significantly influenced the cutting performance. Moreover, the results indicated that depth of cut increased with the increase of waterjet pressure, the decrease of traverse speed, and decrease in standoff distance. Waterjet pressure provided major contribution to depth of cut, followed by traverse speed, then standoff distance, which was demonstrated by both ANOVA and regression analysis. The experimental results showed that when the standoff distance was closer than 10 mm and waterjet pressure was 280 MPa, all maize stalks specimen could be cutoff thoroughly. With the consideration of field operating conditions, waterjet pressure of 280 MPa or higher and 10 mm to 15 mm standoff distance were recommended for maize stalks cutting. This analysis provided a realistic approach for the optimization of the ultra-high pressure pure waterjet parameters in maize stalks cutting, which could be used to relieve the occurrence of straw blockage in no-till planting. Keywords: waterjet, ultra-high pressure, conservation tillage, maize stalks, cutting, traverse speed, standoff distance DOI: 10.25165/j.ijabe.20191205.5088 Citation: Hu H N, Li H W, Wang Q J, He J, Lu C Y, Wang Y B, et al. Performance of waterjet on cutting maize stalks: A preliminary investigation. Int J Agric & Biol Eng, 2019; 12(5): 64–70.